The art of action how leaders close the gaps between plans, actions, and results - Bungay, Stephen (Boston Nicholas Brealey Pub, 2011)
Drawing on his experience as a consultant, senior manager and a highly respected military historian, Stephen Bungay takes a close look at the nineteenth-century Prussian Army, which built its agility on the initiative of its highly empowered junior officers, to show business leaders how they can build more effective, productive organizations. Based on a theoretical framework which has been tested in practice over 150 years, Bungay shows how the approach known as 'mission command' has been applied in businesses as diverse as pharmaceuticals and F1 racing today.
Includes bibliographical references (p. 275-278) and index.
Keywords: Leadership